Prevention of toxoplasmosis during pregnacy: addressed by strategic planning in the Brown Health Centre of General Pico, La Pampa (Veterinary Science, 2017)
Trough the strategic planning it was done a situational diagnosis and a problematic analysis of the health system to implement a interventional project in the Brown Health Centre of the city of general Pico, La Pampa. The objectives were to analyse the characteristic of interventional scenario recognising necessities, health problems and parts. It was selected as a health problem the lack of knowledge of the mechanisms of transmission and prevention of toxoplasmosis in puber and fertile women. To sizing the problem a questionnaire was done to the selected population. As consequence was evidenced an ignorance of the women surveyed in relation to the form of ransmission of toxoplasmosis, and 50% of the pregnant women did not have serum title against the disease turning them in a risk group. It was concluded that social cultural actions tending to spread the knowledge of causes and sources of the toxoplasmosis infection from an inter sectorial perspective and community participation was accurate.
Keywords: Toxoplasmosis; Prevention